Peculiarities of criminal proceedings materials preservation in conditions of martial law - T. H. Fomina (Bulletin of Kharkiv National University of Internal Affairs)
Taking into account the latest legislative changes to the Criminal Procedure Code of Ukraine, the theoretical and practical issues of the preservation of criminal proceedings materials in the conditions of martial law are highlighted. The judicial practice regarding the restoration of lost materials of criminal proceedings has been analyzed. The study of the decisions entered into the Unified State Register of Court Decisions shows that the recovery of criminal proceedings materials is not yet a widespread practice, which is due to several factors. It is emphasized that the restoration of the materials of criminal proceedings in the future will depend on the availability of criminal proceedings material copies at the investigator’s, inquirer’s and prosecutor’s disposal, given that the legislative changes to Art. 615 of the Criminal Procedure Code of Ukraine are quite timely and appropriate.